Focusing on Formononetin: Recent Perspectives for its Neuroprotective Potentials - Tian, Jiao; Wang, Xing-Qin; Tian, Zhen (Frontiers in Pharmacology, 2022)
Nervous system is the most complex system of the human body, hence, the neurological diseases often lack effective treatment strategies. Natural products have the potential to yield unique molecules and produce integrative and synergic effects compared to standard therapy. Mounting evidence has shown that isoflavonoids contained in traditional medicinal plant or dietary supplementation may play a crucial role in the prevention and treatment of neurological diseases due to their pronounced biological activities correlating to nervous system. Formononetin, a non-steroidal isoflavonoid, is a bioactive constituent of numerous medicinal plants such as red clover (Trifolium pratense) and Astragalus membranaceus. Emerging evidence has shown that formononetin possesses considerable anti-inflammatory, antioxidant and anti-cancer effects. This review intends to analyze the neuropharmacological potential of formononetin on the therapy of nervous system disorders. The neuroprotective properties of formononetin are observed in multiple neurological disorders including Alzheimer’s disease, dementia, cerebral ischemia, traumatic brain injury, anxiety and depression. The beneficial effects of formononetin are achieved partially through attenuating neuroinflammation and oxidative stress via the related signaling pathway. Despite its evident effects in numerous preclinical studies, the definite role of formononetin on humans is still less known. More well-designed clinical trials are required to further confirm the neuroprotective efficacy and safety profile of formononetin before its application in clinic.